Comparative effectiveness of azithromycin for treating scrub typhus: A PRISMA-compliant systematic review and meta-analysis. Issue 36 (September 2017) - Lee, Szu-Chia; Cheng, Yu-Jyun; Lin, Chao-Hsu; Lei, Wei-Te; Chang, Hung-Yang; Lee, Ming-Dar; Liu, Jui-Ming; Hsu, Ren-Jun; Chiu, Nan-Chang; Chi, Hsin; Peng, Chun-Chih; Tsai, Te-Lung; et al.
Abstract: Background: Scrub typhus is a zoonotic disease that remains an important health threat in endemic areas. Appropriate anti-rickettsial treatment ensures a successful recovery. Doxycycline is a recommended drug, but it is contraindicated in pregnant women and young children. Azithromycin is a safer alternative drug, but its effectiveness remains largely unclear. Herein, we conducted a systematic review and meta-analysis to determine the effectiveness of azithromycin. Methods: Studies that investigated azithromycin in treating scrub typhus were systematically identified from electronic databases up to December 2016. Information regarding study population, disease severity, treatment protocols, and responses was extracted and analyzed. Results: In this review, 5 studies were included, which comprised a total of 427 patients. When comparing the treatment failure rate, we observed a favorable outcome in patients treated with azithromycin (risk ratio [RR] 0.83, 95% confidence interval [CI] 0.23–2.98). However, patients in the azithromycin group had longer time to defervescence (mean difference 4.38 hours, 95% CI −2.51 to 11.27) and higher rate of fever for more than 48 hours (RR 1.31, 95% CI 0.81–2.12). Moreover, patients treated with azithromycin had less adverse effects (RR 0.8, 95% CI 0.42–1.52). Conclusions: Azithromycin is as effective as other anti-rickettsial drugs with higher treatment success rates, lower frequency of adverse effects, and longer time to defervescence (GRADE 2B). Therefore, it is reasonable to use azithromycin as the first-line treatment against scrub typhus. Further studies are warranted to elucidate the effectiveness of azithromycin in specific patient groups, at high dose and influence of drug resistance. Abstract : Supplemental Digital Content is available in the text